Risk Factors and Incidence of Escherichia coli Producing Extended-spectrum β-lactamase (ESBL) in Dairy Cattle - Dameanti, Fidi Nur Aini Eka Puji; Akramsyah, Muhammad Ali; Hasan, Chyntia Silvi Yanti; Amanda, Jacky Teguh; Pratama, Alfaro Rikko; Fahmiantika, Reza; Tedja, Dhaneswara; Izofani, Safira; Sutrisno, Rahayu (Jurnal Medik Veteriner, 2022)
This study aimed to evaluate the risk factor and insidence of Extended-spectrum b-lactamase (ESBL) produced by Escherichia coli in dairy cattle. The samples obtained were 38 rectal swabs from dairy cows from the Successful Mutual Livestock Group, Deyeng Village, Kediri Regency, East Java. The study started with interviews and observations using a questionnaire to obtain data on risk factors (source of drinking water, cleanliness of feedlots, cleanliness of drinking places, administration of antibiotics, history of mastitis). A sampling of the rectal swab of cattle was carried out using Nutrient Broth as carrier media. Isolation of bacteria using Mac Conkey Agar (MCA) media with the antibiotic cefotaxime 1 mg/L. The addition of antibiotics is intended so that the bacteria that grow are coliform bacteria resistant to the cefotaxime antibiotic, a beta-lactam group. Bacterial isolation was continued with MCA media to enrich ESBL bacteria. Bacterial identification was continued on EMBA media, gram staining, IMViC biochemical test, TSIA, and urease to obtain isolates of E. coli bacteria. The E. coli isolates tested for ESBL Double Disc Synergy Test (DDST) phenotype. The close relationship between each risk factor and the incidence of ESBL-producing E. coli was tested statistically using the Spearman Rank correlation test. The results showed that the incidence of ESBL-producing E. coli in the tested samples was 21.05%, or there were eight positive samples of ESBL-producing E. coli. The risk factors for finding a positive incidence of E. coli producing ESBL in this study were 87% of the use of drinking water sources from wells, 25% did not pay attention to the cleanliness of drinking places, 25% did not pay attention to the cleanliness of eating places, 38% were given antibiotics during maintenance, and 100% had a history of mastitis. These risk factors were not statistically closely related to the incidence of ESBL-producing E. coli.